Institutional determinants of new firm entry in Russia: a cross regional analysis - Randolph Luca Bruno; Maria Bytchkova; Saul Estrin (Institute for the Study of Labor (IZA), 2008)
We analyse a three-year panel data set of Russian firms spanning from 2000 to 2002 and we investigate the effect of regional institutional and economic factors on entry rates across time, industries and regions. The paper builds on a novel database and exploits inter-regional variation in a large number of institutional variables. We find entry rates in Russia are not especially low by international standards and are correlated with natural entry rates, institutions and firm size. Furthermore, industries that - for scale and technological reasons - are characterised by higher entry rates will experience lower entry within regions affected by higher business risk. In other words industries that naturally have low entry barriers are most affected by business constraints.
urn:nbn:de:101:1-20081014287
Keywords: D21; 330; Entry rate; business environment; Tobit model; Markteintritt; Unternehmensgründung; Region; Standortfaktor; Schätzung; Russland